CATEGORIES OF MODAL VERBS - Matmuratova Fauziya (Scholar Express Journals, 2023)
This essay explores the three main categories of modal verbs: ability, possibility, and necessity. It discusses how these categories express different attitudes and viewpoints towards actions or events. The essay provides examples and explanations for each category, highlighting the usage of common modal verbs such as 'can,' 'could,' 'may,' 'might,' 'must,' 'should,' 'ought to,' and 'have to.' It emphasizes that modal verbs do not change based on the subject and are followed by the base form of the main verb, except for 'ought to' and 'have to.' Understanding the categories and usage of modal verbs is crucial for effective communication in English.
Keywords: Modal verbs; ability; possibility; necessity